Lung ultrasonography results statistically agree with computed tomography in COVID-19 pneumonia cases from a private hospital in southern Brazil - Pallarés, Luiz Carlos (2024)
Introduction: Computed tomography (CT) scans can both exclude other pathological conditions and display a high level of sensitivity for COVID-19 pneumonia. Although LUS has the potential to replace these methods in patient evaluation, issues remain as to whether it can be considered a reliable surrogate in the clinical decision process. Objective: To compare the performance of lung ultrasonography (LUS) with that of lung computed tomography (CT) scans in COVID-19 patients for the presence of interstitial pneumonia and the degree of lung injury. Methods: In a cross-sectional clinical study, LUS and CT were compared for the presence of interstitial pneumonia and the degree of lung injury in COVID-19 patients. Pearson’s and Spearman correlations analysis were performed to measure the degree of association between the two methods. Bland–Altman plot was applied. P-values ≤ 0.05 were considered significant. Results: A good correlation between LUS and CT scan was obtained for estimates of lung injury in pneumonia in a group of COVID-19 patients (R2= 0.7613; p <0.01). Agreement between LUS and CT values is assessed by constructing the Bland-Altman plot and most of the data points fall within ± 1.96 times the standard deviation of the difference between the results of the two methods. This corroborates that there is a strong agreement between the two methods. Conclusions: LUS, as compared to CT scans, is an effective method to estimate degrees of lung injury in COVID-19 patients in the emergency department.